Entre os monoteísmos, os atributos divinos e seus problemas cognoscíveis: análise da contribuição do pensamento de Dionísio, o Pseudo-Areopagita, para o problema dos nomes divinos - Sousa, Marcel Alcleante Alexandre de (2020)
The problem of divine names is a theme that resonates in the Middle Ages, as is the problem of universals and other themes. To discuss this problem, Pseudo-Dionísio dedicates a work entitled Nomes Divinos. It is a theological-philosophical contribution to the theme. The work consists in understanding to describe the problem of divine names traced by Pseudo-Dionísio as discursive operations in the relationship of man with the divine. With the phenomenological method one can describe what is most characteristic of an object under study. This step is important for the recognition of the phenomenon being applied the method. Phenomenology allows us to understand the object of study as it appears investigations. The first chapter deals with four monotheisms: Mazdeism; Judaism; Christianity and Islam. It is a contextualization and description of the similarities between them. In the second chapter, the idea of mystique as significant religious experience. Though it should be borne in mind that it is not necessary to be religious to be mystic and to speak of it. The third deals with Pseudo-Dionisio's contribution to the problem of divine names. A chapter that brings intervention from other theorists, but always emphasizes the contribution of a theory to the tradition on the subject. Think about the theme of the problems of divine names in the sciences of religions and remind this field of study that the theme is unique. Although one has the option not to name what is sacred, reality contradicts such a hypothesis. Religious man in his different religious systems appoints. To name means to contain. Contains itself to be able to celebrate.